Transverse vibration of axially loaded beam with parallel-coupled nonlinear isolators. (1st April 2023) - Liu, Wen-Hang; Lu, Ze-Qi; Hao, Rong-Biao; Ding, Hu; Chen, Li-Qun
Highlights: An axially loaded beam with parallel-coupled nonlinear isolation system is modelled. Non- co -location of the excitation source and the isolation object is issued. Double annular magnets and spiral springs aligned on the same axis is used to achieve high static and low dynamic stiffness. The initial axial force load of the axially loaded beam can extend the isolation range. An experiment is implemented to verify the accuracy of the analytical model. Abstract: To improve low-frequency vibration isolation when the excitation source and the isolation object are not co-located, transverse vibration of axially loaded beam with parallel-coupled nonlinear isolators is explored both experimentally and analytically. The nonlinear isolators use double annular magnets and spiral springs aligned on the same axis to achieve high static and low dynamic stiffness, which is suitable for low-frequency vibration isolation. Using the Galerkin truncation, harmonic balance analysis, and arc-length continuation, an approach is developed to analyze the frequency response functions of power flow for the strongly nonlinear discrete and continuum coupled systems. Both analytical and numerical results demonstrate that frequency response function of power flow can be used to deal with transverse vibration which excitation source and isolation object are not co-located. Parallel-coupled nonlinear vibration isolator can decrease the energy transmission of high order modal vibration of continuum, compared with the discrete isolation system. The axially loaded beam with parallel-coupled nonlinear isolators achieves significant vibration suppression at low frequency. Parametric studies of strongly nonlinear discrete and continuum coupled systems demonstrate that increasing the length of the beam and increasing the initial axial force can reduce the resonant frequency, which broadens the vibration isolation frequency band. An experiment is implemented to verify the accuracy of the theoretical model.